Different levels of immunogenicity of two strains of Fowlpox virus as recombinant vaccine vectors eliciting T-cell responses in heterologous prime-boost vaccination strategies. - Cottingham, MG; van Maurik, A; Zago, M; Newton, A; Anderson, R; Howard, M; Schneider, J; Skinner, M (2006)
The FP9 strain of F has been described as a more immunogenic recombinant vaccine vector than the Webster FPV-M (FPW) strain (R. J. Anderson et al., J. Immunol. 172:3094-3100, 2004). This study expands the comparison to include two separate recombinant antigens and multiple, rather than single, independent viral clones derived from the two strains. Dual-poxvirus heterologous prime-boost vaccination regimens using individual clones of recombinant FP9 or FPW in combination with recombinant modified V Ankara expressing the same antigen were evaluated for their ability to elicit T-cell responses against recombinant antigens from Plasmodium berghei (circumsporozoite protein) or human immunodeficiency virus type 1 (a Gag-Pol-Nef fusion protein). Gamma interferon enzyme-linked immunospot assay and fluorescence-activated cell sorting assays of the responses to specific epitopes confirmed the approximately twofold-greater cellular immunogenicity of FP9 compared to FPW, when given as the priming or boosting immunization. Equality of transgene expression in mouse cells infected with the two strains in vitro was verified by Western blotting. Directed partial sequence analysis and PCR analysis of FPW and comparison to available whole-genome sequences revealed that many loci that are mutated in the highly attenuated and culture-adapted FP9 strain are wild type in FPW, including the seven multikilobase deletions. These "passage-specific" alterations are hypothesized to be involved in determining the immunogenicity of fowlpox virus as a recombinant vaccine vector.